Mechanical properties of concrete cubes using tyre waste as partial sand replacement - Eric Jason, Stanley (2019)
Motorcar waste tyre has a steady increase in its generation annually in Malaysia. The number of motorcar waste tyres generated annually in the country was estimated to be 8.2 million or approximately 57,391 tonnes in the year 2006. In addition to this, 60% of the waste tyres are disposed via unknown routes. Waste tyres in Malaysia are neither categorized as solid waste or hazardous waste. Currently it is just generalized as trade waste. Since there isn’t any law or regulation which governs waste tyre management, we have decided to use this material in our research to determine the mechanical properties of concrete after partial sand replacement. Tyre is made of rubber that gives it properties of absorbing shock and therefore having it at a certain percentage in the concrete will eventually give the concrete new properties. The tyre waste used in this research is grinded into powder form and then used partially to replace sand in a concrete mix design to find its suitable percentage to be used to gain the optimum strength. The concrete cubes tested in this research are sized at (150mm x 150mm) each and tested at different percentage of sand replacement. The cubes are casted at a 0% (controlled cube), 5%, 10% and 15%. Each percentage had 9 identical cubes casted to get an average data that was tested on the 7th, 14th and 28th day since it was casted. The tests carried out for these cubes are Ultrasonic Pulse Velocity (UPV) also known as the pundit test, slump test and the compression test. The results from the experiment as of the 28 days shows that at the 7th day compression testing, the cube with 10% sand replacement has the highest concrete strength of 723.1kN, whereas for the 14th day testing the cube with 10% has the highest concrete strength as well at 810.9kN followed by the 28th day that also shows that the cube with 10% sand replacement having the highest concrete strength.